The Influence Of Physical And Chemical Treatments Towards The Colour Stability Of Angkak Extracted Colouring Powder - Nurika, Irnia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2002)
The study is aimed at evaluating the influence of dextrin concentration and spray dryer inlet temperatures on the color stability of the angkak extracted coloring powder. This study was performed using factorial randomized block design, consisting of two factors. The first factor was dextrin concentration i.e. 4.0%, 4.5%, 5.0%, 5.5% and 6.0%, and the second one was spray dryer inlet temperature i.e. 160oC, 165oC, 170oC, 175oC and 180oC. The experiment was in duplicate. The parameters measured were the yield, moisture content, pH, and color intensity as affected by solubility in water, heating temperature, duration of heat, oxidation and reduction agent added, either by neutral and acid pH values. The result showed that dextrin concentration and spray dyer inlet temperature gave significant effect toward color stability. Color intensity (Absorbency/A) of Angkak that dissolved in water in 100oC was 3.553; while of it’s dissolved on 29oC was 3.312. The effect of heating at 150oC for 1 hour was 1.498, and if it is heated at 100o C for 1 hour was 2.517. However, if heated for 1 hour at 100°C it was 2.760, and if heated for 3 hours at 100°C it was 1.928. The addition of reductor agent gave the color intensity of 3.025, while the oxidator gave color intensity of 2.476. At neutral pH value (6.8), the color intensity was 5.579, and at acid pH (3.5) was 4.291. Key words: angkak, color stability, dextrin, extract, spray dryer